Improving the Innovative Activity of the Region with Impact upon Tourism - TOLEPOV, Adil; TLESOVA, Aigul; MOLDASHEVA, Anar; MUSABAEV, Kuat; ORYNBASSAROVA, Yerkenazym; SAPAROVA, Botagoz (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
A necessary condition for the sustainable development of the tourism industry is to attract investment and funding for innovative activities in the field of tourism and the improvement of innovative activities in the region. In the development of the tourism industry, an active state policy and regulatory framework aimed at creating a favorable infrastructure that helps attract investment plays an important role. The international experience also shows that countries actively involved in the development of tourism have a large budget for the implementation of national projects and programs and provide their citizens with high quality tourism services. All this is important for the study, since the development and support of the tourism industry, the development of competition and the attractiveness of investments depend on a large number of factors that reflect the general state of the country's economic policy.